2007
DOI: 10.1080/01926230701748446
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Clinical Chemistry and Microscopic Renal Effects Following Acute Uranyl Acetate Exposure

Abstract: Military use of depleted uranium (DU) has renewed interest in the toxicology of this metal. In this study, the nephrotoxicity of single exposure DU was assessed with and without pre-exposure stress. Adult male Sprague-Dawley rats (n=288) were administered a single IM dose of 0, 0.1, 0.3 or 1.0 mg/kg DU. Corticosterone concentrations (ng/ml, mean+/-SD) were 763.65+/-130.94 and 189.80+/-90.81 for swim stressed and unstressed rats. Serum and kidney uranium concentration, hematocrit, chemistry, and renal histology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Biochemical parameters (creatinine, urea, BUN) were normal compared with control in animals treated with 2 and 4 mg/kg after 1 d and also no histopathological alternations such as tubular damage was observed. A similar study performed on rat showed that at low doses of 0.1, 0.3, and 1 mg/kg (single exposure) of uranyl acetate via intra muscular route did not show any significant increase in serum creatinine and BUN compared with control after 24 h. 15 In contrast, a study on male Wistar rats showed single injection of uranyl acetate at different doses of 0.5, 1, and2 mg/kg, i.p. (single exposure) caused a significant increase in serum blood nitrogen and creatinine levels after 1 d of dosing.…”
Section: Concentration Of Uranium In Kidney Tissuementioning
confidence: 73%
“…Biochemical parameters (creatinine, urea, BUN) were normal compared with control in animals treated with 2 and 4 mg/kg after 1 d and also no histopathological alternations such as tubular damage was observed. A similar study performed on rat showed that at low doses of 0.1, 0.3, and 1 mg/kg (single exposure) of uranyl acetate via intra muscular route did not show any significant increase in serum creatinine and BUN compared with control after 24 h. 15 In contrast, a study on male Wistar rats showed single injection of uranyl acetate at different doses of 0.5, 1, and2 mg/kg, i.p. (single exposure) caused a significant increase in serum blood nitrogen and creatinine levels after 1 d of dosing.…”
Section: Concentration Of Uranium In Kidney Tissuementioning
confidence: 73%
“…Rats exposed to uranyl acetate (1 mg/kg injected) demonstrated tubular necrosis and changes in blood chemistry reflecting renal compromise. After 30 days regeneration had taken place, however, cortical scarring and interstitial nephritis persisted [35]. Treatment of uranium intoxication involves removal of the source of exposure and supportive treatment.…”
Section: Acute High Dose Exposurementioning
confidence: 99%
“…Contamination of groundwater and soil with uranium has resulted from anthropogenic activities such as uranium mining and milling and processing of uranium for nuclear weapons and energy programs [ Wolbarst et al ., ; National Research Council (NRC) , ], as well as from natural processes in rock, soil, and water. Uranium contamination causes health risks and presents serious public health concerns [ Zimmerman et al ., ; NRC , ]. A great deal of resources has been directed toward identifying efficient in situ strategies to remove soluble U(VI) from groundwater, including promotion of in situ biological reduction (see summaries in Fang et al .…”
Section: Introductionmentioning
confidence: 99%